Soft and flexible material-based affinity sensors - Meng, Lingyin; Turner, Anthony P. F.; Mak, Wing Cheung (Elsevier, 2019)
Recent advances in biosensors and point-of-care (PoC) devices are poised to change and expand the delivery of diagnostics from conventional lateral-flow assays and test strips that dominate the market currently, to newly emerging wearable and implantable devices that can provide continuous monitoring. Soft and flexible materials are playing a key role in propelling these trends towards real-time and remote health monitoring. Affinity biosensors have the capability to provide for diagnosis and monitoring of cancerous, cardiovascular, infectious and genetic diseases by the detection of biomarkers using affinity interactions. This review tracks the evolution of affinity sensors from conventional lateral-flow test strips to wearable/implantable devices enabled by soft and flexible materials. Initially, we highlight conventional affinity sensors exploiting membrane and paper materials which have been so successfully applied in point-of-care tests, such as lateral-flow immunoassay strips and emerging microfluidic paper-based devices. We then turn our attention to the multifarious polymer designs that provide both the base materials for sensor designs, such as PDMS, and more advanced functionalised materials that are capable of both recognition and transduction, such as conducting and molecularly imprinted polymers. The subsequent content discusses wearable soft and flexible material-based affinity sensors, classified as flexible and skin-mountable, textile materials-based and contact lens-based affinity sensors. In the final sections, we explore the possibilities for implantable/injectable soft and flexible material-based affinity sensors, including hydrogels, microencapsulated sensors and optical fibers. This area is truly a work in progress and we trust that this review will help pull together the many technological streams that are contributing to the field.
Keywords: Affinity sensors; Point-of-care; Wearable; Implantable; Papers; Conducting polymers; Molecular imprinted polymers; Skin patches; Contact lenses; Hydrogels